Exploring Deixis and Politeness Strategy Committed between Student and Lecturer - Jaul Fadoli (Journal of English Language and Education, 2022)
This current study aims at seeking the type of deixis and politeness strategy often used by student and lecturer. The writer applied a descriptive qualitative research method to explore the phenomena on student and lecturer interaction. The data were primarily collected from student and lecturer chat on WhatsApp and Email. Then, those were analyzed on deixis and politeness theory proposed by Brown and Levinson theory. The research revealed that the occurrences of person deixis and address terms were prevalently committed. As the conclusion, the results of this study might become insight for students as an effort to create effective interaction with their lecturers.